PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT PADA RUS BAHTERAMAS PROVINSI SULAWESI TENGGARA - Handris Handris; Nurwati Nurwati; Sri Wiyati Mahrani; Salma Saleh; Agustinus Tangalayuk; Muhammad Taufik; Asrip Putera (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The effect of compensation, motivation and work environment on the performance of nurses at Bahteramas Hospital, Southeast Sulawesi Province. This research was conducted with the aim of knowing and analyzing the effect of compensation, motivation and work environment on the performance of nurses at Bahteramas Hospital, Southeast Sulawesi Province. This research approach is a quantitative approach. The population of this study was 371 nurses at the Bahteramas Hospital, Southeast Sulawesi Province. The number of samples used in this study amounted to 79 nurses with the random sampling technique. The research model used multiple linear regression analysis with SPSS 20 software.The results showed that partially compensation has a positive and significant effect on performance; motivation has a positive and significant effect on performance. While the work environment has a positive but not significant effect on performance. Simultaneously compensation, motivation and work environment have a positive and significant effect on performance.